2012
DOI: 10.1007/s10549-012-2062-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and pathologic characteristics of BRCA-positive and BRCA-negative male breast cancer patients: results from a collaborative multicenter study in Italy

Abstract: Recently, the number of studies on male breast cancer (MBC) has been increasing. However, as MBC is a rare disease there are difficulties to undertake studies to identify specific MBC subgroups. At present, it is still largely unknown whether BRCA-related breast cancer (BC) in men may display specific characteristics as it is for BRCArelated BC in women. To investigate the clinical-pathologic features of MBC in association with BRCA mutations we established a collaborative Italian Multicenter Study on MBC with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
3
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 76 publications
(80 citation statements)
references
References 24 publications
6
70
3
1
Order By: Relevance
“…The need for more refined therapeutic treatments for male breast cancer (MBC) is evidenced by a steady stream of publications highlighting gender-specific differences using IHC (1-5), genetics (6)(7)(8)(9)(10)(11), and more recently, epigenetics (12)(13)(14)(15). Of note, although MBC is similar histologically to female breast cancer (FBC), with the same panel of biomarkers used to guide treatment and prognosis, more rigorous interrogation of the underlying genetics shows heterogeneity in MBC as recognized in FBC where molecular profiling has identified different subgroups that correlate with varying clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The need for more refined therapeutic treatments for male breast cancer (MBC) is evidenced by a steady stream of publications highlighting gender-specific differences using IHC (1-5), genetics (6)(7)(8)(9)(10)(11), and more recently, epigenetics (12)(13)(14)(15). Of note, although MBC is similar histologically to female breast cancer (FBC), with the same panel of biomarkers used to guide treatment and prognosis, more rigorous interrogation of the underlying genetics shows heterogeneity in MBC as recognized in FBC where molecular profiling has identified different subgroups that correlate with varying clinical outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, we have recently shown that HER2? subtype was associated with BRCA2 mutations in MBC [10]. Although based on small number of cases, these results may suggest that the observed associations between susceptibility loci and ER/ PR status may reflect underlying associations with particular molecular profiles.…”
Section: Discussionmentioning
confidence: 72%
“…All subjects were recruited from ten Italian Investigation Centers distributed across the country in the frame of the ongoing Italian Multicenter Study on MBC [10]. Information collected for each MBC case included: age at diagnosis, family and personal history of cancer, recurrence of the disease, BRCA1/2 mutation status, tumor histological type, grade (G), node (N) status, ER, PR, Ki-67, and HER2 expression.…”
Section: Study Populationmentioning
confidence: 99%
See 2 more Smart Citations